A novel method for preserving cultured limbal epithelial cells. Issue 6 (23rd November 2006) - Utheim, Tor Paaske; Raeder, Sten; Utheim, Øygunn Aass; Cai, Yiqing; Roald, Borghild; Drolsum, Liv; Lyberg, Torstein; Nicolaissen, Bjørn
Abstract : Aim: To investigate organ culture preservation of cultured limbal epithelial cells in order to enhance the availability of tissue-engineered epithelia that are used to treat patients with limbal stem cell deficiency. Methods: Limbal epithelial cells were cultured for 3 weeks on intact amniotic membrane fastened to a polyester membrane carrier. The cultured epithelia were stored for 1 week at 23°C in organ culture medium. The preserved epithelia were then examined using a colorimetric cell viability assay, light microscopy and immunohistochemistry. Results: The viability of the preserved epithelia was 84% (20%), and no statistically significant difference was found compared with non-preserved epithelia. In general, the cell borders were maintained, the nuclei showed no sign of degeneration, and the original layered structure was preserved. Mild intercellular oedema was occasionally observed. Expression of p63, K19 and vimentin was maintained. Conclusions: Cultured limbal epithelial cells can be preserved in organ culture medium for 1 week at room temperature, while maintaining the original layered structure and undifferentiated phenotype.